Coronary artery perforation successfully treated with a second drug-eluting stent - Strycek, Matej; Jaworski, Lukas; Polasek, Rostislav; Tomasov, Pavol (Journal of international medical research, 2023)
A coronary artery perforation is a rare, but potentially lethal, complication of percutaneous coronary intervention. We present a case of massive main vessel coronary perforation of the right coronary artery in a patient with acute ST segment elevation myocardial infarction, which was successfully treated with a second drug-eluting stent. This uncommon therapeutic approach was used to preserve flow to the large side branch. Early recognition, rapid balloon re-inflation at the perforation site and a "ping-pong" guiding technique allowed us to prepare the optimal strategy and to treat the perforation without developing cardiac tamponade.
Keywords: výsledek terapie; infarkt myokardu; koronární cévy; Coronary Vessels; Treatment Outcome; koronární angiografie; koronární angioplastika; Myocardial Infarction; Coronary Angiography; stenty uvolňující léky; lidé; Angioplasty, Balloon, Coronary; Drug-Eluting Stents; Humans; Percutaneous Coronary Intervention; balónková koronární angioplastika